Christian eschatology in Africa in the shadow of Christ-Ancestor - (:unkn) unknown (My University, 2017)
The cultural context of the african continent is marked by the pregnancy of the ancestors.That is why the theology of the inculturation of the faith thought of having to appropriate the theme of the ancestor to repatriate its symbolic meaning in the service of the christian faith. But beyond an informal putting in report between the Christ and the ancestor, the inculturation of the faith evolved towards the speculative formality of an ancestralisation of the Christ. In that respect, the theology of Christ-Ancestor places us in front of a precarious process of logical subsumption which introduces and risks to absorb the Novum of Christ in the categories and the previous kinds of the culture of reception. The ancestralism is not only african reality; it crosses the Bible and the other cultures as that of ancient Rome and ancient China. Beyond the exemplary causality of the ancestor which the memory of past is enough to establish metaphysically, the christian theology cannot recognize it an efficient causality. In christian faith, it is the efficiency of the Resuscitated that upsets all the category of salvific efficiency previous to the Christian novelty. Christ is not an Ancestor, he is Eschaton.
Keywords: African Research